Towards a quantitative analysis of the wettability of microparticles using an automated contact timer apparatus. (1st April 2020) - Hartmann, Robert; Serna-Guerrero, Rodrigo
Graphical abstract: Highlights: Particle-bubble attachment as a function of contact time, distance and wettability. Calculation of drainage force and critical height of the intervening liquid film. Derivation of contact angle of microparticles based on non-compressive attachments. Abstract: The time required for the attachment ( tatt ) between solid particles and bubbles in an aqueous phase is known to reflect the interfacial characteristics of the three-phase system. Although plenty of research has been performed on the use of induction timers to measure tatt, the derivation of quantitative parameters to determine the wettability of microparticles has not been reported so far. Indeed, the use of induction timers has been limited to the estimation of relative floatability of specific systems. Consequently, the objective of this work is to develop a sound methodology to overcome the current limitations of induction timers. In order to provide an adequate method for wettability characterisation, the present work offers a critical analysis on assumptions and experimental procedures previously reported in the literature regarding contact timers. The arbitrary definition of contact times at 50% bubble-particle attachment probability and the negligence of particle-bubble distance during attachment events are of particular concern. Using the novel Automated Contact Timer Apparatus (ACTA), it was found that, for a proper assessment of attachment due to interfacial forces, attachment probabilities should be measured within a zone of non-compressive attachment (NCA). In the absence of compression, only particles with a meaningful hydrophobic character present high attachment probabilities. It is also experimentally demonstrated that the probability of attachment as a function of contact time depends on the final distance between particles and bubbles. Using the right values of particle-bubble attachment probability, a method to deduce three-phase contact angles from induction timer experiments is proposed for the first time. The similarities between contact angles calculated from attachment timer results (i.e, 51° and 88°) and those of analogous flat surfaces with the sessile drop method (i.e, 49° and 78°) prove the applicability and high potential of this methodology to study the wettability of microparticles.